Water Balance for Ali AL-Gharbi-Northeast of Missan Governorate- Southeast of Iraq - Al-Kubaisi , Qusai Y.; Al-Ghurabi, Mariam Y. (Iraqi Journal of Science, 2022)
Ali AL-Gharbi area lies to the northeast of Missan Governorate, southeast of Iraq. The meteorological data recorded in Ali AL-Gharbi station for the period (1994-2014) were used to assess the climatic condition of the study area, it was found that the monthly mean of rainfall is (15.35 mm), relative humidity (43.95 %), the temperature (24.50 C◦), wind speed (4.35 m/sec) and the strongest and most frequent winds are the northwest, sunshine (8.54 h/day) and evaporation (305.73 mm).The results of the data analysis show that, the climate of study area is characterized by dry and relatively hot in summer, and cold with low rain in winter. This study shows that, there is water surplus of (35.69 %) of the total rainfall amount which is equivalent to (184.28 mm), and the amount of surface runoff is (5.12mm), and the amount of groundwater recharge is (60.65mm) from the total rainfall.